Saving spaces - Sprinkle, John H., author.
1 online resource (244 pages)
Keywords: Saving Spaces offers an historical overview of the struggle to conserve both individual parcels of land and entire landscapes from destruction in the United States. John Sprinkle, Jr. identifies the ways in which the identification, evaluation, and stewardship of selected buildings and landscapes reflect contemporary American cultural values. Detailed case studies bring the text to life, highlighting various conservation strategies and suggesting the opportunities, challenges, and consequences of each. Balancing close analyses with a broader introduction to some of the key issues of the field, Saving Spaces is ideal for students and instructors of historic preservation.